2004
DOI: 10.1117/12.553169
|View full text |Cite
|
Sign up to set email alerts
|

The crystal-size and power dependence of luminescence properties of Nd3+:LaAlO 3 nanopowders

Abstract: The luminescence properties of the Nd 3+ :LaAlO 3 nanocrystalline powders characterized by different sizes of grains in the range of 25-50 nm were investigated. The effect of the nanocrystallites sizes on the luminescence behavior of Nd 3+ was observed. In particular decreasing the grain sizes was found to increase emission from the thermally populated 4 F 5/2 state. It's intensity increased with the increase of excitation power density. The spectroscopic parameters of Nd 3+ doped LaAlO 3 nanocrystallites were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…The most intense luminescence of the Nd 3+ originates from the de-excitation of the 4 F 3/2 multiplet. In general, the results are consistent with those reported by Strek et al for nanopowders of the Nd 3+ doped LaAlO 3 obtained by the modified Pechini method. The comparison of the luminescence behavior of the Nd:LaAlO 3 single crystals described in detail by Dereń et al revealed the significant difference in the intensity ratio of the 4 F 3/2 → 4 I 9/2 and 4 F 3/2 → 4 I 11/2 .…”
Section: Resultssupporting
confidence: 92%
“…The most intense luminescence of the Nd 3+ originates from the de-excitation of the 4 F 3/2 multiplet. In general, the results are consistent with those reported by Strek et al for nanopowders of the Nd 3+ doped LaAlO 3 obtained by the modified Pechini method. The comparison of the luminescence behavior of the Nd:LaAlO 3 single crystals described in detail by Dereń et al revealed the significant difference in the intensity ratio of the 4 F 3/2 → 4 I 9/2 and 4 F 3/2 → 4 I 11/2 .…”
Section: Resultssupporting
confidence: 92%
“…The increase of synthetic parameters, like concentration of Nd 3+ cations and sintering temperature, leads to the emission spectra comparable with the ground single crystal. Similar results were observed for the other type of nanoparticles whose host lattices show anisotropy of optical properties. , …”
Section: Resultssupporting
confidence: 84%
“…Similar results were observed for the other type of nanoparticles whose host lattices show anisotropy of optical properties. 32,33 The size effect is also reflected in the presence of the socalled hot emission band related to the ( 4 F 5/2 , 2 H 9/2 ) → 4 I 9/2 transitions (see inset in Figure 6, right). 34 This type of emission is the result of thermalization of the 4 F 3/2 level and promotion of electrons to the upper 4 F 5/2 , 2 H 9/2 levels.…”
Section: Resultsmentioning
confidence: 99%